2015
DOI: 10.1073/pnas.1514123113
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoylation controls DLK localization, interactions and activity to ensure effective axonal injury signaling

Abstract: Dual leucine-zipper kinase (DLK) is critical for axon-to-soma retrograde signaling following nerve injury. However, it is unknown how DLK, a predicted soluble kinase, conveys long-distance signals and why homologous kinases cannot compensate for loss of DLK. Here, we report that DLK, but not homologous kinases, is palmitoylated at a conserved site adjacent to its kinase domain. Using short-hairpin RNA knockdown/rescue, we find that palmitoylation is critical for DLK-dependent retrograde signaling in sensory ax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
238
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 105 publications
(263 citation statements)
references
References 57 publications
25
238
0
Order By: Relevance
“…In peripheral neurons JNK3 plays key roles in retrograde responses to axonal injury and was previously reported to colocalize with JIP3 on axonal vesicles (Keramaris et al, 2005, Cavalli et al, 2005). It is thus tempting to speculate that palmitoylation accounts for this vesicular targeting of JNK3 and that these JNK3-JIP3-positive vesicles are similar, or perhaps identical, to the recently reported DLK-JIP3 positive vesicles (Holland et al, 2016). If so, then palmitoylation would play a key role in modifying multiple DLK-JNK pathway components to ensure the specificity and transport of neuronal injury signals.…”
Section: Additional Roles For Palmitoylation In Dlk-jnk Pathway Signasupporting
confidence: 72%
See 3 more Smart Citations
“…In peripheral neurons JNK3 plays key roles in retrograde responses to axonal injury and was previously reported to colocalize with JIP3 on axonal vesicles (Keramaris et al, 2005, Cavalli et al, 2005). It is thus tempting to speculate that palmitoylation accounts for this vesicular targeting of JNK3 and that these JNK3-JIP3-positive vesicles are similar, or perhaps identical, to the recently reported DLK-JIP3 positive vesicles (Holland et al, 2016). If so, then palmitoylation would play a key role in modifying multiple DLK-JNK pathway components to ensure the specificity and transport of neuronal injury signals.…”
Section: Additional Roles For Palmitoylation In Dlk-jnk Pathway Signasupporting
confidence: 72%
“…However, it had been unknown how DLK, a predicted soluble kinase, conveys these long-distance signals. Recently, DLK was found to be palmitoylated at a conserved site adjacent to its kinase domain (Holland et al, 2016). ShRNA knockdown/rescue experiments, in which endogenous DLK in sensory neurons was replaced with a palmitoyl-site mutant, revealed that palmitoylation at this site is critical for DLK-dependent retrograde injury signaling (Holland et al, 2016) (Figure 3).…”
Section: New Roles For Palmitoyl-kinases In the Peripheral Nervous Symentioning
confidence: 99%
See 2 more Smart Citations
“…Palmitoylation is required for EZH2 targeting to the Golgi apparatus, where phosphorylation occurs. ZDHHC5 is localized to detergent-resistant microdomains of the plasma membrane (18); palmitoylation is necessary for vesicle trafficking and for the formation of EZH2 multiprotein complexes (40).…”
Section: Discussionmentioning
confidence: 99%